Image quality of a novel light-emitting diode (LED)-illuminated colonoscope - Sasaki, Sho; Nishikawa, Jun; Yanai, Hideo; Nakamura, Munetaka; Nishimura, Junichi; Goto, Atsushi; Kiyotoki, Shu; Saito, Mari; Hamabe, Kouichi; Tanabe, Ryo; Nakamura, Yohei; Tokiyama, Hiroshi; Hashimoto, Shinichi; Okamoto, Takeshi; Higaki, Shingo; Kurai, Satoshi; Ogihara, Hiroyuki; Hamamoto, Yoshihiko; Sakaida, Isao (Endoscopy, 2016)
Background and study aims: Light-emitting diodes (LEDs) are used widely for their high luminous efficiency and durability. We developed a novel prototype high definition endoscope with white LEDs and evaluated the image quality it produced against a commercial endoscope with conventional light source.Patients and methods: The specifications of both colonoscopes were identical, except for the LED light source at the tip of the prototype. We examined 20 patients with rectal or sigmoid colon lesions and the image quality was evaluated in 40 images (one image from the LED colonoscope and one from the conventional colonoscope for each lesion) by three endoscopists. We additionally evaluated the 17 videos recorded with the LED colonoscope that were available. Image quality, mucosal and vascular color, and luminous distribution and intensity were scored on a 5-point scale. Results: The mean score for vascular color given by one evaluator was significantly higher using the LED colonoscope than using the conventional colonoscope. The mean scores for mucosal color and luminous intensity from another evaluator were significantly lower with the LED colonoscope than with the conventional colonoscope. There were no significant differences in the luminous distribution scores for any of the evaluators. The image quality of the videos was evaluated as being similar with both colonoscopes. Conclusions: Image quality from the LED and conventional colonoscopes were similar, although the luminous intensity of the LEDs is inferior to that of the conventional light source at the present time.